WAKAF UANG PERSPEKTIF SYARIAH DAN HUKUM POSITIF DI INDONESIA - Nasikhin; Ulul Albab (Sekolah Tinggi Ilmu Syariah Al-Hilal Sigli Aceh- Indonesia, 2022)
This study aims to explore the views of sharia and positive lawregarding cash waqf. The results of the study indicate that theissue of waqf in Indonesia is enshrined in Government Regulationnumber 28 of 1977. While according to sharia there is no verse inthe Qur'an that clearly explains the concept of cash waqf. Becausewaqf is included in the infaq fi sabilillah group, the basis used byscholars in explaining and explaining the concept of waqf is basedon the generality of the verses of the Qur'an about infaq. Theproblems of developing cash waqf in Indonesia can be highlightedin three aspects consisting of human resources, trust, system andsharia. can be done to develop cash waqf in Indonesia. Thesestrategies include transparency and accountability at every stageof implementation, more computerized cash waqf management,improving the quality of more comprehensive managers, and theestablishment of waqf educational institutions.